TIME TO DTR: FAN PARATEXTUALIZATION ABOUT GAME OF THRONES’ LAST SEASON - Bruno Melo Moura (Revista de Administração da Universidade Federal de Santa Maria, 2022)
Purpose: The meaning of media products lies on the way their content is interpreted, since fans reframe them as productive consumers. They produce new texts - known as paratexts - about these products throughout this process. The aim of the current research is to investigate how fans’ paratexts (re)produce discourses to re-signify media products’ (para)texts. In order to do so, we analyzed the fan paratextualization of Game of Thrones (GoT), which was an economic and cultural phenomenon that has significantly echoed in social media. Design/methodology/approach: Based on the Foucauldian Archeology, we collected and analyzed comments posted by GoT fans in promotional videos published in the TV series’ official YouTube channel. Findings: Fans’ paratextual production has evidenced different positions about the cultural product consumed by them. Among them, one finds a public tribute highlighting its cultural legacy, which was based on feelings such as nostalgia and frustration with the way its plot was concluded. Thus, it is possible saying that these paratexts worked as reckoning for fans of this TV series. In broader terms, it is possible interpreting paratexts as the marketing content enabling fans to act as prosumers towards media products, the entertainment industry and fans’ culture.Originality/value: The current study investigates how fans’ productive consumption takes place through paratext (re)production to establish the echo of media objects in fans’ culture and to enable them to play the role of co-authors of texts consumed by themselves. This role reinforces that fans should be understood as consumers who can act freely, without taking into consideration marketing actions. Moreover, it implies that paratexts can be produced to boost the discursive production, which works as fans’ prosumer performance.